(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The development of the literary and artistic process, the entry of the art of speech into a new era, shows that certain changes are taking place in the structure of the story in terms of form and content. This phenomenon is manifested, including in Uzbek prose. Such developments are visible not only in the story, but also in the artistic device of the novel, which is considered a large epic form. In the later stages of modern Uzbek storytelling, in particular, during the years of national independence, one can see a slight increase in attention to the objectivity of the image in the area of the artistic text. Such a creative and poetic renewal is also visible in the research and experiments of Shukur Kholmirzayev, Erkin A’zam, Nazar Eshonkul in the field of storytelling. The article, through the study of some stories, discusses the connection between the main features of the human image in samples of the small epic genre - his personality, inner world, social and personal activities, and many factors.